Pharmacological Characterization of the Native Store-Operated Calcium Channels of Cortical Neurons from Embryonic Mouse Brain - Chauvet, Sylvain; Jarvis, Louis; Chevallet, Mireille; Shrestha, Niroj; Groschner, Klaus; Bouron, Alexandre (Frontiers in Pharmacology, 2016)
In the murine brain, the first post-mitotic cortical neurons formed during embryogenesis express store-operated channels (SOCs) sensitive to Pyr3, initially proposed as a blocker of the transient receptor potential channel of C type 3 (TRPC3 channel). However, Pyr3 does not discriminate between Orai and TRPC3 channels, questioning the contribution of TRPC3 in SOCs. This study was undertaken to clarify the molecular identity and the pharmacological profile of native SOCs from E13 cortical neurons. The mRNA expression of STIM1-2 and Orai1-3 was assessed by quantitative reverse transcription polymerase chain reaction. E13 cortical neurons expressed STIM1-2 mRNAs, with STIM2 being the predominant isoform. Only transcripts of Orai2 were found but no Orai1 and Orai3 mRNAs. Blockers of Orai and TRPC channels (Pyr6, Pyr10, EVP4593, SAR7334, and GSK-7975A) were used to further characterize the endogenous SOCs. Their activity was recorded using the fluorescent Ca2+ probe Fluo-4. Cortical SOCs were sensitive to the Orai blockers Pyr6 and GSK-7975A, as well as to EVP4593, zinc, copper, and gadolinium ions, the latter one being the most potent SOCs blocker tested (IC50 ∼10 nM). SOCs were insensitive to the TRPC channel blockers Pyr10 and SAR7334. In addition, preventing mitochondrial Ca2+ uptake inhibited SOCs which were unaffected by inhibitors of the Ca2+-independent phospholipase A2. Altogether, Orai2 channels are present at the beginning of the embryonic murine cortico-genesis and form the core component of native SOCs in the immature cortex. This Ca2+ route is likely to play a role in the formation of the brain cortex.